Unified Resource Allocation and Mobility Management Technique Using Particle Swarm Optimization for VLC Networks - Muhammet Selim Demir; Sadiq M. Sait; Murat Uysal (IEEE Photonics Journal)
In this paper, we present a unified resource allocation and mobility management algorithm based on particle swarm optimization (PSO) for indoor visible light communication (VLC) networks. We consider a VLC network where multiple LEDs serve as access points (APs). A centralized controller collects channel state information, quality of service requirements of the users, and the overload status of the APs. Based on the available information, in each time interval, the controller decides which user is served by which AP and assigns subcarriers to the users with the objective of maximizing both the system throughput and user satisfaction. We formulate the resource allocation problem as a constrained nonlinear integer programming problem and solve it using meta-heuristic PSO. Through an extensive simulation study, the superiority of the proposed algorithm in terms of system throughput and user satisfaction over round robin, best channel quality information, and genetic algorithms is demonstrated.